Karakteristik pasien reaksi kusta di Rumah Sakit Umum Pusat H. Adam Malik Medan periode tahun 2009 – 2012 - Teguh Aly’ansyah; Syahril R. Lubis; Richard Hutapea (Fakultas Kedokteran USU, 2013)
Introduction : Leprosy is a chronic infection disease, caused by Mycobacterium leprae, involved skin and peripheral nerves, but also other organs or system, except central nerves.To determine the characteristics of leprosy reaction patients in H. Adam Malik General Hospital Medan in the period of 2009- 2012.Methods : A retrospective study was performed based on the medical records of leprosy reaction patients from January 2009 to December 2012.Results : There were 42 cases of leprosy reactions, 31 male and 11 female. Most of the cases was found at the age of 25-34 years old group (16 cases). The majority of the ethnic is Batak (21 cases), the education is high school graduate (15 cases). Leprosy reaction most suffered by labour (10 cases), type of leprosy is MB leprosy (33 cases), type of leprosy reaction is type 2 (26 cases) and onset of leprosy reaction is during the treatment of MDT (22 cases).Conclusion : Leprosy reaction in H. Adam Malik General Hospital Medan Hospital more prevalent in male, age group 25-34 years, the ethnics are Batak, high school graduate, civil servant laour. Most leprosy reaction is MB leprosy, type 2 leprosy reaction and during the treatment.Keywords : leprosy reaction; retrospective study; characteristic